2018
DOI: 10.1097/aap.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Levels and Length of Intraoperative Controlled Hypotension and Acute Kidney Injury in Total Hip Arthroplasty Patients Receiving Neuraxial Anesthesia

Abstract: In this study, AKI was rare. We found a lack of association between IOH and postoperative AKI in a setting where neuraxial anesthesia-facilitated IOCH is routinely practiced. Therefore, it seems prudent for future research and clinical guidelines to consider the distinction between inadvertent and controlled hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Six studies [9,10,11,12,13,14] were subsequently excluded because they did not use standard AKI definitions of Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease (RIFLE), Acute Kidney Injury Network (AKIN), and Kidney Disease: Improving Global Outcomes (KDIGO) classifications. Thus, 17 cohort studies [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,37] comprising 24,158 patients undergoing THA were included into the meta-analysis of associated AKI incidence. The literature retrieval, review, and selection process are demonstrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies [9,10,11,12,13,14] were subsequently excluded because they did not use standard AKI definitions of Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease (RIFLE), Acute Kidney Injury Network (AKIN), and Kidney Disease: Improving Global Outcomes (KDIGO) classifications. Thus, 17 cohort studies [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,37] comprising 24,158 patients undergoing THA were included into the meta-analysis of associated AKI incidence. The literature retrieval, review, and selection process are demonstrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Reported risk factors for AKI in patients undergoing THA are demonstrated in Table 2 [18,19,20,22,23,24,26,27,29,30,31,32,33,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. Older age [23,24,26,29,31,55,60], higher body mass index (BMI) [19,22,23,24,26,30,31,46,47,48,49,56,57,59], reduced baseline estimated glomerular filtration rate (eGFR)/chronic kidney disease (CKD) [31,54,55,57,60], diabetes mellitus (DM) [24,26,31,34,47,55,57], nonsteroidal anti-inflammatory drug (NSAID) [23,32,53] use, and perioperative blood transfusion [23,47,53,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations